Ответ:
Пошаговое объяснение:
2/3 × х + 3целых 4/5 = 3целых 2/3
2/3 × х = 3целых 2/3 - 3целых 4/5
2/3 × х = 3целых 10/15 - 3целых 12/15
2/3 × х = -2/15
х = -2/15 ÷ 1/3
х = -2/15 × 3/1
х = -2/5 × 1/1
х = -2/5 или -0,4
5целых 5/6 ÷ 3целых 1/2 = х ÷ 15
35/6 ÷ 7/2 = х ÷ 15
35/6 × 2/7 = х ÷ 15
5/3 × 1/1 = х ÷ 15
5/3 = х ÷ 15
х = 5/3 × 15
х = 5/1 × 5
х = 25
х ÷ 16 = 3целых 3/4 ÷ 6целых 2/3
х ÷ 16 = 15/4 ÷ 20/2
х ÷ 16 = 15/4 × 2/20
х ÷ 16 = 3/2 × 1/4
х ÷ 16 = 3/8
х = 3/8 × 16
х = 3/1 × 2
х = 6
(х - 0,18) ÷ 0,02 = 3
х - 0,18 = 3 × 0,02
х - 0,18 = 0,06
х = 0,06 + 0,18
х = 0,24
(8х + 2,4) ÷ 3 = 1,8
8х + 2,4 = 1,8 × 3
8х + 2,4 = 5,4
8х = 5,4 - 2,4
8х = 3
х = 3 ÷ 8
х = 3/8
-0,2х × (-0,7) = 0,84
-0,2х = 0,84 ÷ (-0,7)
-0,2х = -1,2
х = -1,2 ÷ (-0,2)
х = 6
1/3 × х + 2целых 2/5 = 3целых 2/3
1/3 × х = 3целых 2/3 - 2целых 2/5
1/3 × х = 3целых 10/15 - 2целых 6/15
1/3 × х = 1целая 4/15
х = 1целая 4/15 ÷ 1/3
х = 19/5 × 3/1
х = 57/5
х = 11целых 2/5 или 11,4
Объяснение:
a/16=4
a=16*4
a=64
Три четвёртых числа 120 = 90
3/7-1/2=6/14-7/14=-1/14
5 3/4:(-1/14)=23/4*
(-14)=-161/2=-80.5
3*1 2/15=3*17/15=17/5=3.4
-80.5-3.4=-83.9